2016
DOI: 10.1002/cbic.201600096
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Measurement of Inositol 1,4,5‐Trisphosphate by Using a New Fluorescent Ligand and Ligand Binding Domain Combination

Abstract: Based on the results of our previous adenophostin A structure-activity relationship studies, two fluorescent inositol 1,4,5-trisphosphate (IP3 ) receptor ligands, fluorescent adenophostin A (FADA) and fluorescent low-affinity ligand (FLL), were designed. Binding of the fluorescent ligands to the fluorescent IP3 sensor in protein-expressing cells caused FRET. This principle was extended to a cell-free assay system by using the fluorescent IP3 sensor bound to agarose beads. The effect of FLL on the FRET signal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
8
0
2
Order By: Relevance
“…In a subset of simulations, we have replaced our non-cooperative IP 3 R model, in which the binding of a single IP 3 site is enough to open the monomer channel, with the cooperative model proposed by Bicknell and collaborators [84]. With 100 nM basal IP 3 and Ca 2+ [85, 86], we could not produce spontaneous calcium signals in these conditions, even after a search of the parameter space to locate parameters allowing spontaneous activity with this cooperative model. This issue might reflect a general problem of the De Young Keizer model in discrete particle-based models with low copy number of particles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a subset of simulations, we have replaced our non-cooperative IP 3 R model, in which the binding of a single IP 3 site is enough to open the monomer channel, with the cooperative model proposed by Bicknell and collaborators [84]. With 100 nM basal IP 3 and Ca 2+ [85, 86], we could not produce spontaneous calcium signals in these conditions, even after a search of the parameter space to locate parameters allowing spontaneous activity with this cooperative model. This issue might reflect a general problem of the De Young Keizer model in discrete particle-based models with low copy number of particles.…”
Section: Discussionmentioning
confidence: 99%
“…γ and α values were adjusted to yield basal calcium concentration around 120 nM [86, 124]. Likewise, β and μ were adjusted for a basal IP 3 concentration of 120nM [85]. Note that this value is based on recent, precise measurements of IP 3 concentration and differs by an order of magnitude from IP 3 concentration values routinely used in IP 3 R -mediated calcium models [59, 125, 126].…”
Section: Methodsmentioning
confidence: 99%
“…We showed that IP3, as well as AdA, could interfere with BH4-Bcl-2 binding to the LBD of IP3R1. To address the opposite question, namely whether BH4-Bcl-2 might affect the interaction of IP3 with the LBD, we performed FRET-based measurements using a competitive fluorescent ligand assay for IP3 [46]. In this method, binding of a fluorescent low-affinity ligand (FLL) and a fluorescent IP3-binding protein (CFP-coupled LBD) generates FRET signals.…”
Section: C)mentioning
confidence: 99%
“…C)にルイス酸存在下における C-アリル化 の結果を示すように,ラジカル反応だけでなくの S N 1 型 C-グリコシル化にも適用できる. 89,91) さらに は O-グリコシル化へも適用可能であり,IP 3 受容体 リガンド 12 及び 14(Fig. 15)の a-O-グリコシド 結 合 は , 本 法 を 用 い て 高 立 体 選 択 的 に 構 築 し た.49,50,52) …”
unclassified
“…Fig. 15) . 43 52) その結果,IP 3 様の Ca 2+ 動 員活性を持つ 13, 47) IP 3 受容体サブタイプ I 選択的 アゴニスト 14, 50) バイオツール合成前駆体 1549,52) …”
unclassified